The Meaning of Consuming Halal Products According to Muslim Millennial Generation in Realizing Of Maqasid Sharia “Maslahah” - Mursal - Mursal; Muhammad Fauzi; Alan Rakhmat Putra; Al Mahdi (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose  – This study aims to explore the meaning of the concept of halal product consumption by millennial Muslims as part of their identity and lifestyle. The main focus is to understand how millennial Muslims interpret halal product consumption not only as a religious rule but also as a symbol of quality, and social identity. Method – The research method used is quantitative and qualitative, qualitative data collection using in-depth interviews with 10 informants and supported by survey data from 70 millennial Muslim generation respondents with purposive sample techniques. The respondents came from students of the Sharia Faculty of IAIN Kerinci, Study Program "Islamic Law and Sharia Economic Law", semester 7 and above. The population was 120 students using a questionnaire instrument with 10 question items. The data were analyzed to identify the main themes related to the meaning of the concept of halal product consumption in everyday life Result –The results of the study show that millennial Muslims have a broader meaning of halal, including aspects of sustainability, ethics, and health. Halal is no longer limited to food, but has become a lifestyle that includes the beauty, fashion, and financial sectors. This generation sees halal products as a marker of identity, allowing them to express their religious commitment in modern society. In addition, halal is also seen as a symbol of quality and safety that provides a sense of comfort in social interactions, thus attracting both Muslim and non-Muslim consumers. Implication – As a practical implication, the results of this study can be used as one of the information for halal industry researchers. This study provides a picture that halal has transformed into a symbolic direction and is in the midst of society.